Analisis Penerapan Tarif Jasa Rawat Inap Kelas NAPZA Dengan Metode Activity Based Costing Pada Rumah Sakit Jiwa Daerah Atma Husada Mahakam - Danna Solihin, 3, Radika Rahim Eddy Soegiarto 2 (EKONOMIA, 2020)
ABSTRACT Analysis of the Application of Service Rates for Inpatient Classes with Activity Based Costing at the Atma Husada Mahakam Regional Mental Hospital.               The formulation of this problem is whether calculating the rate of inpatient treatment for class III drugs applied at the Atma Husada Mahakam Regional Mental Hospital is higher than calculating the rates using the Activity Based Costing method. This study aims to study the calculation of the cost of inpatient treatment for class III drugs applied at the Atma Husada Mahakam Regional Mental Hospital higher than calculating the rates with the Activity Based Costing method..               The analysis method used is a comparative descriptive method that shows and compares the rates of hospital hospitalization with traditional methods and the Activity Based Costing method.               The results of the calculation of inpatient rates with the Activity Based Costing method in class III drug provide higher results compared to the traditional method applied by the Atma Husada Mahakam Regional Mental Hospital, with a difference of Rp 104,205.68. This can occur because all costs are calculated based on consumption which raises costs.            Tariif differences that occur due to the imposition of costs on the Activity Based Costing method for the activities of each room are different and use more then one cost driver and overhead costs on the activity based costing method not based on volume, but on the activities required.